The Conceptual Change of Conscience Franz Wieacker and German Legal Historiography 1933-1968 - Erkkilä, Ville (Mohr Siebeck, 2019)
How did the drastic experiences of the turbulent twentieth century affect the works of a legal historian? What kind of an impact did they have on the ideas of justice and rule of law prominent in legal historiography? Ville Erkkilä analyses the way in which the concepts of 'Rechtsgewissen' and 'Rechtsbewusstsein' evolved over time in the works of the prestigious legal historian Franz Wieacker. With the help of previously unavailable sources such as private correspondence, the author reveals how Franz Wieacker's personal experiences intertwined in his legal historiography with the tradition of legal science as well as the social and political destinies of twentieth century Germany.